Pierce Similarity Algorithm In Detection Of Jar Letter In Al-Quran As Basic Media For Learning Arabic Language Structure - Miftahul Jannah; Adli Abdillah Nababan (Universitas Medan Area, 2021)
Al-Quran is the basic reason someone should understand the rules of Arabic. One of the basic rules is knowing the jar type which we generally often encounter in Arabic, but we do not understand that this letter has its own duties and functions. In this study, samples of Jar letters were used as many as 7 jar letter patterns which are generally often encountered in the Al-Quran. The purpose of this research is to build a system that can recognize Jar letters using the Pierce Similarity method and performs the performance on the algorithm. The research method used is the theory of pattern recognition in image processing with 2 processes, namely the Training Process and the Testing Process. The value of each letter pattern obtained in the Training Process will be the weight benchmark for the Testing Process, so that we can measure the performance level of Algortima Pierce Similarity in detecting the Jar letter pattern. The results can vary for each letter pattern ranging from 60% to 80%.